CONCEPT OF PROTECTION AGAINST COMPUTER VIRUSES AND DETECTION PERFORMANCE Trojan trojan virus - Maria Sri Wulandari (Majalah SIKOMTEK, 2005)
Computer security is not considered important by many people apparently can take a big lossfor that person. If further research proved many things - things that can threaten data -personal data through computer media. There is now a lot of programs - programs that aremalicious as viruses, worms, trojans and other when infecting our computer system mayresult in losses for us. Trojan Horse or better known as the